A gate evaluation of the sources of error in quantitative90Y PET. Issue 10 (6th September 2016) - Strydhorst, Jared; Carlier, Thomas; Dieudonné, Arnaud; Conti, Maurizio; Buvat, Irène
Abstract : Purpose: Accurate reconstruction of the dose delivered by 90 Y microspheres using a postembolization PET scan would permit the establishment of more accurate dose–response relationships for treatment of hepatocellular carcinoma with 90 Y. However, the quality of the PET data obtained is compromised by several factors, including poor count statistics and a very high random fraction. This work uses Monte Carlo simulations to investigate what impact factors other than low count statistics have on the quantification of 90 Y PET. Methods: PET acquisitions of two phantoms—a NEMA PET phantom and the NEMA IEC PET body phantom‐containing either 90 Y or 18 F were simulated usinggate . Simulated projections were created with subsets of the simulation data allowing the contributions of random, scatter, and LSO background to be independently evaluated. The simulated projections were reconstructed using the commercial software for the simulated scanner, and the quantitative accuracy of the reconstruction and the contrast recovery of the reconstructed images were evaluated. Results: The quantitative accuracy of the 90 Y reconstructions were not strongly influenced by the high random fraction present in the projection data, and the activity concentration was recovered to within 5% of the known value. The contrast recovery measured for simulated 90 Y data was slightly poorer than that for simulated 18 F data with similar count statistics. However, the degradation was not strongly linked to any particular factor. Using a more restricted energy range to reduce the random fraction in the projections had no significant effect. Conclusions: Simulations of 90 Y PET confirm that quantitative 90 Y is achievable with the same approach as that used for 18 F, and that there is likely very little margin for improvement by attempting to model aspects unique to 90 Y, such as the much higher random fraction or the presence of bremsstrahlung in the singles data.